Climate‐Associated Genetic Variation and Projected Genetic Offsets for Cryptomeria japonica D. Don Under Future Climate Scenarios - Kentaro Uchiyama; Tokuko Ujino‐Ihara; Katsuhiro Nakao; Jumpei Toriyama; Shoji Hashimoto; Yoshihiko Tsumura (Evolutionary Applications)
ABSTRACT Revealing the spatial distribution of adaptive genetic variation is both a challenging and crucial task in evolutionary ecology, essential for understanding local adaptation within species, and in management, for predicting species responses to future climate change. This understanding is particularly important for long‐lived tree species, which may not be able to migrate quickly enough to adapt to rapid climate changes and may need to rely on their standing genetic variation. In this study, we focused on Cryptomeria japonica, a major component of Japan's temperate forests and an important forestry species adapted to the humid environment of monsoon Asia. We extracted climate‐associated genetic variation from the entire genome and evaluated its distribution and vulnerability under future climate scenarios using spatial modeling techniques. We analyzed 31,676 high‐quality SNPs from 249 individuals across 22 natural populations of C. japonica, covering its entire distribution range. We identified 239 candidate climate‐associated SNPs and found winter temperature, summer precipitation, and winter precipitation as the most significant factors explaining the genetic variation in these SNPs. The climate‐associated genetic variation deviated from non‐associated (neutral) genetic variation in the opposite (the Sea of Japan and Pacific Ocean) sides of Japanese archipelago, suggesting natural selection of different climate conditions in these regions. Difference in estimated allele frequency at the climate‐associated loci (genetic offset) between the present and future (2090 in the SSP5‐8.5 scenario) climate conditions was predicted to be larger in three areas (not only southwestern Japan but also coastal area on the Sea of Japan side and inland area on the Pacific Ocean side in northeastern Japan). This prediction implies the discrepancy between standing genetic variation at the present and that adaptive to the future climate in these areas, which underscores the necessity for proactive management to adjust the adaptive genetic variation.